Six cases report of differential diagnosis of periapical diseases - Xia, Wen-wei (Nature Publishing Group, 2011)
The distinction of some particular forms of periapical area, involving diseases from regular periapical disease, is a matter of considerable importance when choosing a correct treatment. The aim of this study is to describe the differential diagnosis of periapical diseases from six rare cases in clinical practice. The six rare cases are examples of situations where it is difficult to make a differential diagnosis in clinical practice. By retrospective surveys on the clinical examination, radiographs and pathological results, six patients referred to endodontic treatment in our department were analyzed for the accuracy of diagnosis and therapy. The pathoses of the six cases included two atypical radical cysts, periapical cemental dysplasia, cemento-ossifying fibroma, thymus cancer metastasis in the periapical site and tuberculosis. This report indicates that endodontists should be cognizant of a few particular circumstances when clinically treating periapical diseases.